2015
DOI: 10.1002/dev.21303
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in neurocognitive development in the first two years of life

Abstract: Socioeconomic status (SES) is strongly associated with cognition and achievement. Socioeconomic disparities in language and memory skills have been reported from elementary school through adolescence. Less is known about the extent to which such disparities emerge in infancy. Here, 179 infants from socioeconomically diverse families were recruited. Using a cohort-sequential design, 90 infants were followed at 9 and 15 months, and 89 were followed at 15 and 21 months. SES disparities in developmental trajectori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
120
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 97 publications
(110 reference statements)
6
120
1
2
Order By: Relevance
“…Prior studies suggest that socioeconomic status is associated with neurodevelopment [5] and elevated morning cortisol in very young children [11]. The current findings replicate and extend that work by showing that socio-demographic stress is associated with child cognitive development as early as 15 months.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Prior studies suggest that socioeconomic status is associated with neurodevelopment [5] and elevated morning cortisol in very young children [11]. The current findings replicate and extend that work by showing that socio-demographic stress is associated with child cognitive development as early as 15 months.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have shown that the endogenous release of glucocorticoids affects memory and executive aspects of human cognition [3] however key developmental questions remain. The effects of stress on neurodevelopment are thought to be evident in the first years of life [4,5] and it follows that HPA activity may also be associated with cognitive development during this time. This has not yet been confirmed, as research concerning HPA activity and cognition has been based primarily on studies of older children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…16 There is strong evidence that poverty influences language (tied to the temporal lobe) and executive functioning (related to the frontal lobe). 1719 Deficits in the executive functioning of individuals in poverty have been found during the life course in studies conducted during infancy 20 as well as in childhood, adolescence, 21 and adulthood. 22 Motivated by these findings, a growing number of studies have used neuroimaging and found smaller volumes in the frontal and temporal lobes for children and adolescents living in poverty.…”
Section: Brain Plasticity and Environments Of Povertymentioning
confidence: 99%
“…Not surprisingly, recent research suggests that socioeconomic circumstances may have a more nuanced effect on verbal ability than previously thought (Mol & Neuman 2014, Noble et al 2015 and that there is wide variability even within socioeconomic strata (Hoff 2013, Hirsh-Pasek et al 2015a. Contemporary theorists of language socialization have also voiced legitimate concerns about scholarly emphasis on the verbal limitations of children from low-income families without considering areas of strength (Miller & Sperry 2012, Johnson 2015, Sperry et al 2015, as well as the need for widespread adoption of ethnographic approaches that are sensitive to cultural variation (Ochs & Schieffelin 1984).…”
Section: Introductionmentioning
confidence: 98%